(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The researcher dealt with the origins of diction and its concept in the first section, and how the primitive man began to imitate nature and imitate its sounds, and from these sounds the word arose and then the language that represents the important and main link of communication and communication between members of society and the expression through which emotions, feelings and sensory perceptions within each person, as dealt with in the topic The second is the problems that the actors encounter when reciting the standard Arabic language, and how the environment and the different dialects can affect the reciting of the Arabic language, and how the exercises of the articulation organs of the lips, teeth, tongue and throat can have a great impact on being able to pronounce the Arabic language properly and free from impurities of colloquial dialects. and environmentalKeywords: problematic. diction. for the representative. theatrical Iraqi.Iraqi